The impact of the Blue Drop certification programme in Tzaneen municipality within Mopani District municipality Sekhukhune District municipality and Tshwane Metropolitan municipality following its inception as an Incentive Based Regulation since 2008 to improve drinking water quality management - Claassen, Marius (University of Pretoria, 2017)
Dissertation (MSc)--University of Pretoria, 2016.